The Islamic perspective of applicability of the precautionary principle in international trade in GMOS/LMOS - Ansari, Abdul Haseeb; Zainudin, Zaki (AENSI Publications, 2013)
In order to ensure continued supply to ever - growing population, especially in developing and least developed countries, enough prod uction of genetically modified agricultural crops are sine qua non. It is for this reason that agricultural biotechnology has been supplied priority and is getting all kinds of support from governments. But almost all GM foods have their origin in western countries, especially from a multinational company by the name of Monsanto of the United States. These countries are marking their GM products both at national and international levels. Although Islam requires for all edibles to be permissible (halal) and good for human consumption (tayyib), which has been accentuated in form of the precautionary principle – which has been enshrined in several international and national legal instruments, which has to be observed by producing and importing countries and whi ch has to be environmentally friendly – but producing countries do not ensure the safety of biotech food. The precautionary principle has further been strengthened by various Shari‘ah, principles. This paper demonstrates the Islamic perspective of the prec autionary principle and argues for its internalization and practice in international trades in GMOs and GM food.